2013
DOI: 10.1371/journal.pone.0069818
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Grape Polyphenols Supplementation on Endothelial Function in Adults: Meta-Analyses of Controlled Trials

Abstract: BackgroundThe acute effects of grape polyphenols on endothelial function in adults are inconsistent. Here, we performed meta-analyses to determine these acute effects as measured by flow-mediated dilation (FMD).MethodsTrials were searched in PubMed, Embase and the Cochrane Library database. Summary estimates of weighted mean differences (WMDs) and 95% CIs were obtained by using random-effects models. Meta-regression and subgroup analyses were performed to identify the source of heterogeneity. The protocol deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 49 publications
(79 reference statements)
3
20
2
Order By: Relevance
“…Furthermore, a recent review of human clinical studies on the effect of moderate alcohol consumption on cardiovascular disease confirmed that wine and beer seem to have greater cardiovascular protection than spirits due to their polyphenolic content (Chiva-Blanch et al, 2013), lending further support to the ''French paradox'' paradigm (Catalgol et al, 2012). Finally, the results of a recent metaanalysis showed that the acute effect of grape polyphenols on FMD was more significant in subjects with a smoking history or coronary heart disease compared to healthy subjects (Li et al, 2013). Recent studies in which the effect of chronic consumption of polyphenols berries (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, a recent review of human clinical studies on the effect of moderate alcohol consumption on cardiovascular disease confirmed that wine and beer seem to have greater cardiovascular protection than spirits due to their polyphenolic content (Chiva-Blanch et al, 2013), lending further support to the ''French paradox'' paradigm (Catalgol et al, 2012). Finally, the results of a recent metaanalysis showed that the acute effect of grape polyphenols on FMD was more significant in subjects with a smoking history or coronary heart disease compared to healthy subjects (Li et al, 2013). Recent studies in which the effect of chronic consumption of polyphenols berries (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have demonstrated that polyphenols enhance the production of nitric oxide (NO) thus increasing vasodilation (Stoclet et al 2004). A meta-analysis that included nine studies demonstrated that grape polyphenols increase flow-mediated vasodilation compared to controls (Li et al 2013).…”
Section: Epidemiological Informationmentioning
confidence: 99%
“…However, other studies using more practical doses (corresponding to 1.25 g to 2 cups fresh grapes) with standardized grape products have found similar results, increasing the FMD response after both acute and chronic intakes, compared to placebo (Chaves et al 2009;Barona et al 2012). Interestingly, a metaanalysis (described in the previous section) presenting the results of nine controlled trials on the acute effects of grape polyphenol consumption on FMD found that the FMD response significantly increased in the initial 2 h after intake of grape polyphenols as compared with controls, with a peak effect at 30 min in healthy participants compared to a more pronounce but delayed peak at 60 min in volunteers with cardiovascular risk factors (Li et al 2013). The authors proposed that in these subjects with high cardiovascular risk factors, endothelial cells have been impaired and might require 60 min after the ingestion of grape polyphenols to produce adequate nitric oxide to improve endothelial function, resulting in the delayed effect.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Grape consumption and its derivatives are associated with several beneficial health effects, such as: the increase of antioxidant capacity, reduction of oxidized low density lipoproteins (LDL), increase of high density lipoproteins (HDL) (EVANS et al, 2014), improvement of endothelial function (LI et al, 2013) antimutagenic activity (POLONIO et al, 2014), decrease in platelet aggregation (SCHAMATT et al, 2013), and improvement of cardiovascular oxidation (HORT et al, 2012) and neurocognitive function (KRIKORIAN et al, 2012).…”
Section: Introductionmentioning
confidence: 99%